Microbial community structure and functional metabolic diversity are associated with organic carbon availability in an agricultural soil - Juan LI; Yan-ting LI; Xiang-dong YANG; Jian-jun ZHANG; Zhi-an LIN; Bing-qiang ZHAO (Journal of Integrative Agriculture, 2015)
Exploration of soil environmental characteristics governing soil microbial community structure and activity may improve our understanding of biogeochemical processes and soil quality. The impact of soil environmental characteristics especially organic carbon availability after 15-yr different organic and inorganic fertilizer inputs on soil bacterial community structure and functional metabolic diversity of soil microbial communities were evaluated in a 15-yr fertilizer experiment in Chang-ping County, Beijing, China. The experiment was a wheat-maize rotation system which was established in 1991 including four different fertilizer treatments. These treatments included: a non-amended control (CK), a commonly used application rate of inorganic fertilizer treatment (NPK); a commonly used application rate of inorganic fertilizer with swine manure incorporated treatment (NPKM), and a commonly used application rate of inorganic fertilizer with maize straw incorporated treatment (NPKS). Denaturing gradient gel electrophoresis (DGGE) of the 16S rRNA gene was used to determine the bacterial community structure and single carbon source utilization profiles were determined to characterize the microbial community functional metabolic diversity of different fertilizer treatments using Biolog Eco plates. The results indicated that long-term fertilized treatments significantly increased soil bacterial community structure compared to CK. The use of inorganic fertilizer with organic amendments incorporated for long term (NPKM, NPKS) significantly promoted soil bacterial structure than the application of inorganic fertilizer only (NPK), and NPKM treatment was the most important driver for increases in the soil microbial community richness (S) and structural diversity (H). Overall utilization of carbon sources by soil microbial communities (average well color development, AWCD) and microbial substrate utilization diversity and evenness indices (H’ and E) indicated that long-term inorganic fertilizer with organic amendments incorporated (NPKM, NPKS) could significantly stimulate soil microbial metabolic activity and functional diversity relative to CK, while no differences of them were found between NPKS and NPK treatments. Principal component analysis (PCA) based on carbon source utilization profiles also showed significant separation of soil microbial community under long-term fertilization regimes and NPKM treatment was significantly separated from the other three treatments primarily according to the higher microbial utilization of carbohydrates, carboxylic acids, polymers, phenolic compounds, and amino acid, while higher utilization of amines/amides differed soil microbial community in NPKS treatment from those in the other three treatments. Redundancy analysis (RDA) indicated that soil organic carbon (SOC) availability, especially soil microbial biomass carbon (Cmic) and Cmic/SOC ratio are the key factors of soil environmental characteristics contributing to the increase of both soil microbial community structure and functional metabolic diversity in the long-term fertilization trial. Our results showed that long-term inorganic fertilizer and swine manure application could significantly improve soil bacterial community structure and soil microbial metabolic activity through the increases in SOC availability, which could provide insights into the sustainable management of China's soil resource.